p Pengaruh model pembelajaran Terintegrasi Problem Based Learning dan Numbered Head Together Terhadap Hasil Belajar dan Berpikir Kritis Ssiswa Kelas X SMA Negeri 16 Samarinda: Pengaruh model pembelajaran Terintegrasi Problem Based Learning dan Numbered Head Together Terhadap Hasil Belajar dan Berpikir Kritis Ssiswa Kelas X SMA Negeri 16 Samarinda - Indriani, Yeni; Kurniawati, Zenia Lutfi; Masitah; Lumowa, Sonja V.T (PendIPA Journal of Science Education, 2024)
This classroom action research aimed to determine the learning outcomes and level of critical thinking demonstrated by the students in the class. The researchers utilized a quasi-experimental study methodology, especially employing a research design called the one group pretest-posttest design. The methodology used was the Independent Sample t-Test to analyze learning outcomes, with a significance level of 5%. This research results a substantial significance. The two-tailed test result is statistically significant because the p-value (0.000) is smaller than the significance level (0.05), or the t-statistic (3.268) is larger than the crucial t-value (2.01063). This study suggests that the combined use of integrated problem-based learning (PBL) and numbered head together (NHT) learning models significantly affect the learning outcomes of class X students at SMA Negeri 16 Samarinda.